A confirmatory factor analysis model of adversity quotient of five year courses’ 3rd year teacher student at Prince of Songkla University, Pattani campus - หนกหลัง สุเมษย์; ศรีสวนแตง สันติ; ตันพิชัย ประสงค์ (Journal of Liberal Arts Prince of Songkla University, 2025)
The purpose of this research was to examine the goodness of fit model between the adversity quotient among students in a teacher education program and empirical data. Data were collected from 411 third year students in the five-year teacher education course at Prince of Songkla University, Pattani Campus in the academic year 2012 using a 1-5 rating scale questionnaire with 25 question items. Thequestionnaire tested by seven experts had item objective congruence (IOC) between .50-1.00, item discrimination (r.) between 0.224- 0.503 and reliability (a). of 0.87. The data were analyzed with second order confirmatory factor analysis. The results were that the adversity quotient among students in a teacher education program consisted of five main factors: 1. control, 2. causes, 3. responsibility, 4. unde rstanding, and 5. patience, and each of these factors consisted of five ind icators which were consistent with the empirical data: = 354.78, df = 257, p-value < .05; Relative = 1.38; GFI = .94; AGFI = .92; RMR = .06; SRMR = .04; RMSEA = .03; P-Value for Test of Close Fit = 1.00; NFI = .94; IFI = .99; CFI = .99; CN = 348.52. The weight of each factor was be tween .49-.75, and the standard weight of each indicator was between .48-.77.